UNIMAS English language ESL, trainee teachers' beliefs about grammar and grammar teaching - Jesse, Kong. (Universiti Malaysia Sarawak, UNIMAS, 2008)
The aim for this research is to investigate UNIMAS English language ESL trainee teachers regarding their beliefs on grammar and the teaching of grammar. This survey is a cross-sectional study with samples drawn from a total of 74 participants, consisting of 42 pre-service and 32 in-service trainee teachers who are pursuing a degree in Universiti Malaysia Sarawak (UNIMAS). The criteria for the selection of the samples are those trainee teachers have completed their teaching practicum in schools, therefore their beliefs and practices in grammar teaching can be studied as they have been put through theory and practice. There are three research objectives formulated from this study: (1) investigate UNIMAS English language trainee teachers’ beliefs with regards to grammar and grammar teaching, (2) investigate their grammar teaching practices and (3) identify the influences that shaped their beliefs. There are three instruments used to investigate those beliefs and practices. The first instrument is a questionnaire consisting of eight open-ended belief statements used to indicate the teachers’ level of beliefs towards grammar and grammar teaching. The second instrument is semi-structured interview while the third instrument is content analysis of the trainee teachers’ lesson plans to examine their grammar teaching practices. The survey research design used for this study begins with distribution of questionnaires, conducting interviews and finally the content analysis of the lesson plans. From the data analysis, the beliefs systems of UNIMAS trainee teachers are closely tied to the overt grammar. There are positive responses in questionnaires, interviews and content analysis that show strong preference towards overt grammar teaching. However, even though the participants do not reject the notion of covert grammar teaching as implied in the questionnaire, this notion is hardly supported in their interviews and in their content analysis of lesson plans. In terms of their grammar teaching practices, the overt grammar instruction is more prevalent. For the influences that may have shaped their beliefs, two factors were inferred. One of the factors is the teachers that taught those trainee teachers in schools, and the other factor is the level of proficiency of the students that they are teaching.